A new approach to the study of adaptogenic properties of medicinal plants - Гаркава, К. Г. (Problems of Environmental Biotechnology, 2013)
In this paper we studied the adaptogenic properties of medicinal plants: cinnamon rose (Rosa cinnamomea L), prickly hawthorn (Crataegus oxyacantha), tutsan (Hypericum perforatum L.) and red clover (Trifolium pratense L.), their effects on phagocytosis and receptor expression on lymphocytes, as well as evaluated the fatty acid composition of these plants. Results showed that the studied plants did not change phagocytic index of leukocytes and phagocytic number was significantly increased under the influence of cinnamon rose, prickly hawthorn and tutsan. Level of CD3 and CD22 receptors expression remained at control values. Fatty acid composition of plants differed by their level of saturation. Flowers of red clover and tutsan had a smaller percentage of unsaturated and polyunsaturated fatty acids compared with cinnamon hips and prickly hawthorn.